Rapamycin regulates autophagy and cell adhesion in induced pluripotent stem cells - Areechun Sotthibundhu; Katya McDonagh; Alexander von Kriegsheim; Amaya Garcia-Munoz; Agnieszka Klawiter; Kerry Thompson; Kapil Dev Chauhan; Janusz Krawczyk; Veronica McInerney; Peter Dockery; Michael J. Devine; Tilo Kunath; et al. (Stem Cell Research & Therapy, 2016)
Abstract Background Cellular reprogramming is a stressful process, which requires cells to engulf somatic features and produce and maintain stemness machineries. Autophagy is a process to degrade unwanted proteins and is required for the derivation of induced pluripotent stem cells (iPSCs). However, the role of autophagy during iPSC maintenance remains undefined. Methods Human iPSCs were investigated by microscopy, immunofluorescence, and immunoblotting to detect autophagy machinery. Cells were treated with rapamycin to activate autophagy and with bafilomycin to block autophagy during iPSC maintenance. High concentrations of rapamycin treatment unexpectedly resulted in spontaneous formation of round floating spheres of uniform size, which were analyzed for differentiation into three germ layers. Mass spectrometry was deployed to reveal altered protein expression and pathways associated with rapamycin treatment. Results We demonstrate that human iPSCs express high basal levels of autophagy, including key components of APMKα, ULK1/2, BECLIN-1, ATG13, ATG101, ATG12, ATG3, ATG5, and LC3B. Block of autophagy by bafilomycin induces iPSC death and rapamycin attenuates the bafilomycin effect. Rapamycin treatment upregulates autophagy in iPSCs in a dose/time-dependent manner. High concentration of rapamycin reduces NANOG expression and induces spontaneous formation of round and uniformly sized embryoid bodies (EBs) with accelerated differentiation into three germ layers. Mass spectrometry analysis identifies actin cytoskeleton and adherens junctions as the major targets of rapamycin in mediating iPSC detachment and differentiation. Conclusions High levels of basal autophagy activity are present during iPSC derivation and maintenance. Rapamycin alters expression of actin cytoskeleton and adherens junctions, induces uniform EB formation, and accelerates differentiation. IPSCs are sensitive to enzyme dissociation and require a lengthy differentiation time. The shape and size of EBs also play a role in the heterogeneity of end cell products. This research therefore highlights the potential of rapamycin in producing uniform EBs and in shortening iPSC differentiation duration.